Whole Segment Processes in Dogri - Devina Krishna (JURNAL ARBITRER, 2023)
The present paper aims to discuss the phonological processes including whole segment processes occurring in Dogri. It serves an introduction to the types of phonological processes and present examples from Dogri words exhibiting these processes and phenomena. The objective of the present work is to present a complete classification of different phonological processes in Dogri, explore these processes in detail and to acquaint students and researchers with the changes in the sound structure because of the whole segment processes. The earlier linguistic literature on Dogri mentions that various whole segment processes such as gemination, nasalization, addition, deletion, metathesis, substitution, and assimilation were prevalent in Dogri. Moreover, gemination and nasalization is phonemic in Dogri. It has been found that in certain lexical items, transposition of sounds takes place that is one sound is moved next to the adjacent sound and that in turn is replaced by the former sound. In sum, Dogri has been found to make use of a wide variety of the phonological processes. The work employs exploratory research design with thrust on qualitative method involving interpretative approach towards the data. The finding of the research presents a good amount of whole segment and phonological type phonological processes in Dogri lexical items. The study makes students and researchers acquainted with different phonological processes in words and the data serves as a documented record for future researchers and linguists.